The Instrumentation of Standard Diet Food Portions for Diabetes Mellitus - Puspita, Widyana Laksmi; Khayan, Khayan; Hariyadi, Didik; Anwar, Taufik; Wardoyo, Slamet (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
The right diet is needed in the treatment of Diabetes Mellitus. The dietary standards used must be by their nutritional adequacy. This study aims to determine the effectiveness of the use of aluminum cup serving tools for standard measuring devices in the Diabetes mellitus diet. The portion measurement instrument is designed by 1P, 1 1 / 2P, and 2P standards. The study was conducted at a laboratory scale in 2018 with a quasi-experimental approach. Data analysis uses Analysis of Variance (ANOVA) with α = 5%. The results show that the average effectiveness of 1P portion accuracy is 99%, 1½ P for 101%, and 2P about 99.6%. There was no difference in effectiveness compared to using a scale and there were differences in measurements using bowls and spoons. Standard portion of 1P measuring instruments 114% effectiveness bowl and 113% spoon, standard 1½ P portion for 107% bowl and 105% spoon, and 2P standard portion for measuring the effectiveness of the portion of the bowl is 104% and 103% spoon. Using a measuring device Aluminum cup portions, both 1P, 1.5P, and 2P parts can determine the value of food and nutritional adequacy standards of patients with Diabetes Mellitus.